Aerobic post-treatment of anaerobic digested sludge with a focus on organic matter stability and the fate of antibiotic resistance genes. (20th March 2021) - Lin, Zhi; Wu, Zong-Lin; Sun, Zhao-Yong; Gou, Min; Xia, Zi-Yuan; Tang, Yue-Qin
Abstract: Digested residue remains after anaerobic digestion of municipal sludge (hereafter called anaerobic digested sludge, ADS) and needs further treatment to attain more sustainability. In this study, the compostability of ADS was assessed, focusing on the stability of organic matter and the fate of typical antibiotic resistance genes (ARGs). The results showed that ADS was not suitable as a fertilizer (reflected by a low germination index of 16.9%) due to very high concentrations of NH4 + and soluble total organic carbon. Composting post-treatment stabilized the ADS; the degradation efficiency of volatile total solids reached 18.5% within 37 d of composting. The physicochemical properties of the treated ADS indicated that a mature compost product was obtained. Real-time quantitative polymerase chain reaction analysis of typical ARGs revealed that ARG abundance was reduced four-fold during ADS composting due to a reduction in the typical ARGs and low horizontal gene transfer in host microbes. The analysis of bacterial communities revealed that members of the phyla Actinobacteria, Proteobacteria, Firmicutes, Bacteroidetes, and Chloroflexi are crucial for material transformation and ARG reduction during the ADS composting process. These results demonstrated that aerobic composting further stabilized the organic matter and reduced ARG abundance; therefore, it was found to be an effective method for ADS post-treatment. Highlights: Anaerobic digested sludge (ADS) was post-treated via aerobic composting. Unstable ADS was converted to a matured compost product. Typical antibiotic resistance genes (ARGs) abundance was reduced 4-fold. Reduction of ARGs caused by shrink of ARGs hosts and low horizontal gene transfer.